Correlation of Osteocalcin with Vitamin D Level in Postmenopausal Women Concerning CYP24A1 and VDR Gene Polymorphisms - Abdulrahman, Noor Mohammed; Ali, Shatha Hussein (AL-Kindy College Medical Journal, 2024)
Background: Vitamin D is an essential agent in regulating body enzymes due to the wide distribution of vitamin D receptors throughout the body, the site where vitamin D acts. Vitamin D deficiency could be related to many factors. Polymorphism in receptor(s) and enzyme(s) responsible for vitamin D metabolism, like CYP24A1, could be liable for vitamin D deficiency.Objective: This study aims to determine the impact of polymorphism in Vitamin D Receptor TaqI (rs731236) and CYP24A1 (rs2762934 and rs4809957) on vitamin D level and osteocalcin in postmenopausal women.Subjects and Methods: Forty postmenopausal osteoporotic women (patients’ group) according to WHO osteoporosis diagnostic criteria were enrolled in the study. This group received 50000 IU/week of vitamin D for eight weeks. In addition, 30 postmenopausal non-osteoporotic women were set to be a control group. Genetic and biochemical analyses were applied for both groups.Results: Serum levels of osteocalcin in the patients’ group were 9±6.19 and 4±6.6 in groups with vitamin D levels below 20nmole/L and above 20nmole/L, respectively, with a non-significant difference between them (p=0.49). Related to allele frequency, the A/G genotype of rs731236 of the vitamin D receptor, G/G genotype of rs2762934, and A/A genotype of rs4809957 of CYP24A1 showed non-significant differences among the study patients’ group.Conclusions: Our data indicates that rs731236 with the A/G genotype, rs2762934 with the G/G genotype, and rs4809957 with the A/A genotype were more prevalent than the other genotypes and could be responsible for being osteoporotic through their effect on vitamin D level and resistance to vitamin D supplementations.